Supplementation of astaxanthin and vitamin E in feed on the development of gonads white shrimp broodstock Litopenaeus vannamei Boone 1931 - Fajar Maulana; Harton Arfah; Mita Istifarini; Mia Setiawati (Jurnal Akuakultur Indonesia, 2017)
ABSTRACT